The economic value of conservation: Some empirical results - Daniel Shefer; Eyal Salinger (European Regional Science Association (ERSA), 2010)
While conservation of privately owned buildings is produced by the private market, the benefit from conservation accrues not only to the estate of the building's owners, but also to the society at large. Conservation usually requires public involvement, as often market forces do not economically justify the conservation of buildings. The purpose of this research is to identify and estimate the factors affecting the private sector's (building owners') decision whether and when to invest in conservation. This decision is directly concerned as much with the profitability of the investment as with the economic state of the country, in particular housing market conditions (whether there is a demand or a supply surplus), the location of the property, and externalities (adjacent buildings and local infrastructure). We examined the case of the White City of Tel Aviv, which UNESCO declared a World Heritage Site in 2003 because of its outstanding architectural ensemble representative of the Modern Movement in a new cultural context. Data was collected on building's physical attributes, planning regulations applied to the plot, current and historical legal rights status, transactions, and date of conservation, if took place. The decision by building owners whether to invest in conservation and the economic value of conservation on the private market is examined using qualitative and quantitative models. The Logit Model and the Nested Logit Model were used in order to estimate the probability of a decision to conserve. The Hedonic Price Model was used in order to estimate the effect of conservation on the property value. The Real Option - Pricing Model was used in order to estimate whether the value of buildings not yet conserved includes an option component - the option to wait for the optimal timing in carrying out the conservation. We conducted a comparative analysis between buildings designated for conservation and buildings in the same area that needed renovation. The results of this research could assist public policy in promoting the conservation of cultural heritage that we wish to bequeath for future generations.
Keywords: 330